Preventing Malaysia's Traditional Music from disappearing - Lim, Connie Keh Nie; Mohd Fadzil, Abdul Rahman (SEAMEO Regional Centre, 2011)
Connie Lim Keh Nie and Mohamad Fadzil Abdul Rahman discuss how instrumental music performed in the past by the indigenous tribes in Sarawak, are gradually vanishing, or merging with contemporary musical styles, transforming to a modern fusion of ethnic folk music. The authors touch on the diversification of Malaysia’s traditional music, and the approaches adopted by composers and arrangers.